2015
DOI: 10.1002/2014ea000073
|View full text |Cite
|
Sign up to set email alerts
|

Dust deposition on the decks of the Mars Exploration Rovers: 10 years of dust dynamics on the Panoramic Camera calibration targets

Abstract: The Panoramic Cameras on NASA's Mars Exploration Rovers have each returned more than 17,000 images of their calibration targets. In order to make optimal use of this data set for reflectance calibration, a correction must be made for the presence of air fall dust. Here we present an improved dust correction procedure based on a two‐layer scattering model, and we present a dust reflectance spectrum derived from long‐term trends in the data set. The dust on the calibration targets appears brighter than dusty are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 88 publications
2
67
0
Order By: Relevance
“…The model treats single-scattering events in full detail and uses a two-stream formalism [e.g., Zdunkowski et al, 2007] to treat multiple-scattering events. The dust model and procedure follows very closely the one described in full detail in Kinch et al [2015], the only difference is that we here do not distinguish between diffuse sky irradiance and solar (directional) irradiance; rather, all irradiance is assumed to come from the direction of the Sun. The utility of this model for analysis of dusty caltarget surfaces was demonstrated by Johnson et al [2006] in laboratory studies.…”
Section: Improved Flatfieldingmentioning
confidence: 99%
See 1 more Smart Citation
“…The model treats single-scattering events in full detail and uses a two-stream formalism [e.g., Zdunkowski et al, 2007] to treat multiple-scattering events. The dust model and procedure follows very closely the one described in full detail in Kinch et al [2015], the only difference is that we here do not distinguish between diffuse sky irradiance and solar (directional) irradiance; rather, all irradiance is assumed to come from the direction of the Sun. The utility of this model for analysis of dusty caltarget surfaces was demonstrated by Johnson et al [2006] in laboratory studies.…”
Section: Improved Flatfieldingmentioning
confidence: 99%
“…The utility of this model for analysis of dusty caltarget surfaces was demonstrated by Johnson et al [2006] in laboratory studies. A similar, but simpler, two-stream scattering model is currently used for dust correction on the Mars Exploration Rovers' Pancam [Kinch et al, 2007], but work is ongoing to employ this more sophisticated model on that mission as well [Kinch et al, 2015]. Preliminary work on employing this dust model for the MSL Mastcam was presented in Kinch et al [2013].…”
Section: Improved Flatfieldingmentioning
confidence: 99%
“…However, many aspects of seasonal wind activity may be inferred from other instruments. Pancam images (Bell et al, ) of the rover deck obtained over a period of 5 MY indicated that there was a repeating pattern of dust deposition during late northern winter and early spring, peaking at L s = ~45°, and a slightly less regular peak in deposition during late southern winter and early spring, peaking at L s = ~225° (Kinch et al, ). During the periods leading up to these depositional peaks, winds were weak enough to prevent settled dust from being reentrained.…”
Section: Resultsmentioning
confidence: 99%
“…Several previous works point out anomalies in R7 images relative to other filters of the Pancam system. In a study of dust deposition on the Pancam radiometric calibration target (Kinch et al, ), it was found that derived dust albedo values showed a dramatic upturn at the longest wavelength (Figure 8 and section 4.1.2 of Kinch et al, ). The authors also find that the ratio between direct and diffuse illumination showed a dramatic downturn at the longest wavelength (Figure 10 and section 4.2.2 of Kinch et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors also find that the ratio between direct and diffuse illumination showed a dramatic downturn at the longest wavelength (Figure 10 and section 4.2.2 of Kinch et al, ). The authors hypothesize that these observations are caused at least partly by an instrumental artifact and mention under “future work” that this issue is in need of further characterization (section 5.4 of Kinch et al, ).…”
Section: Introductionmentioning
confidence: 99%